La biodégradation de plastique par les bactéries. - Hadda, Khayra.; Bellahmer, Larbi.; Ikhlef, Nacreddine (My University, 2018)
Humanity lives in a business-driven system pushing the production and mass consumption of single-use plastic packaging products. About 90% of the plastic produced to date has not been recycled. As a result, the flow of plastics into our environment has reached the crisis level, and the devastating impact of this pollution is observed in the oceans where ends each year between 8 and 12 million tons of plastic waste. The aim of this work was to select bacteria that degrade plastic material. These strain isolated and identified are gram-positive bacilli capable of growing in temperature of 37° C using the plastic polymer as their carbon source. Only one isolate has been identified as bacillus megaterium by some biochemical tests and by the API 20E gallery. The property analyzed in this study was the potential for bacterial biofilm formation on plastic and its physical characteristics before and after incubation for two months.
Keywords: Biodegradation; Biofilm; Plastic; Bacillus megaterium; Biodegradation; Biofilm; plastique; bacillus mégatérium